Aerosol Products from The Future Space Lidar AEOLUS - Martinet Pauline; Dabas Alain; Lever Vincent; Flamant Pierre; Huber Dorit (EPJ Web of Conferences, 2016)
Ready for launch by the end of 2016, the Doppler lidar mission AEOLUS from the European Space Agency (ESA) will be the first High-Spectral Resolution Lidar (HSRL) in space. Operating in the UV, it implements two detection channels for aerosol and molecular backscatter. The system is primarily designed for the measurement of winds, but the HSRL capability enables the measurement of the particulate backscatter and extinction coefficients without any a priori assumption on the aerosol type. The level-2A (L2A) processor has been developed for these measurements and tested with synthetic data. The results show good aerosol backscatter profiles can be retrieved. Extinction coefficients are reasonable but do not reach the quality of backscatter coefficients. A precise, full, radiometric calibration of the lidar is required. A major limitation of the system is a single polarization component of the light is detected leading to an underestimation of backscatter coefficients when the atmospheric particles are depolarizing. The vertical resolution goes from 250 meters in the lowest part of the atmosphere, to 2 km in the lower stratosphere. The maximum altitude can reach above 20km. The basic horizontal averaging is 90km. Averaging on shorter distances (down to a few km) are possible but require a sufficient signal to noise ratio.